The Effect of Human Development Index (HDI), School Participation Rate (APS) and Labor Force Participation Rate (TPAK) on Poverty Rate, Case Study: Kediri Regency in 2010-2024 - Arsharil Novan Novan; Heny Musfidah; Muhammad Abdul Ghofur (Journal of Economic Education, 2026)
This study aims to examine the influence of Human Development Index (HDI), School Participation Rate (APS), and Labor Force Participation Rate (TPAK) on poverty levels in Kediri Regency during the period 2010-2024. The method used is multiple linear regression with secondary time series data, analyzed using statistical software to test causal relationships among variables. The results show that IPM and APS have a significant negative effect on poverty levels, while TPAK does not have a statistically significant effect. These findings underscore the importance of improving education quality and human development to reduce poverty rates, as well as the need for employment policies that can create productive job opportunities. This study provides empirical contributions to the literature on poverty alleviation using a long-term quantitative approach at the regency level. Furthermore, the study offers practical recommendations for local governments in formulating effective strategies to reduce poverty.